Additional educational needs in children born to mothers with epilepsy. Issue 1 (1st January 2001) - Adab, N; Jacoby, A; Smith, D; Chadwick, D
Abstract : OBJECTIVES: To examine the relative risks of additional educational needs (AENs) in children exposed to antiepileptic drug (AED) monotherapy and polytherapy regimes in utero. METHODS: A retrospective survey of women between the ages of 16 to 40 registered at the Mersey Regional Epilepsy Clinic, who received a postal questionnaire concerning their experience of pregnancy and the subsequent schooling of live-born children. RESULTS: 721 (57%) women of the 1267 approached returned an adequately completed questionnaire; 330 (46%) had given birth to at least one live-born child. Information was collected on 594 children, 400 of whom were of school age (4–18). 150 (37.5%) had been exposed to monotherapy in utero, 74 (18.5%) were exposed to polytherapy, and 176 were not exposed to any AEDs. The odds ratio of AENs for all children exposed to AEDs in utero compared with those unexposed was 1.49 (95% confidence interval (95% CI) 0.83 -2.67). Odds ratios for AENs for each therapy subgroup compared with those unexposed were also calculated for all children. Those exposed to valproate monotherapy had an odds ratio of 3.4 (95% CI 1.63–7.10) by contrast with an odds ratio of 0.26 (95% CI 0.06- 1.15) for carbamazepine. Polytherapy including valproate had similarly high odds ratios for AENs compared with those unexposed of 2.51 ( 95% CI 1.04–6.07) versus the odds ratio of 1.51 ( 95% CI 0.56–4.07) for polytherapy excluding valproate. CONCLUSIONS: Although the findings should be treated with caution, they suggest that monotherapy or polytherapy with valproate during pregnancy carries particular risks for the development of children exposed in utero.